Transition from two wide to a narrow QRS complex tachycardia: What is the mechanism of tachycardia and transition? - Tunçez, Abdullah; Merovci, İdriz; Efe, Tolga Han; Kara, Meryem; Deveci, Bülent; Özcan Çetin, Elif Hande; Korkmaz, Ahmet; Özeke, Özcan; Çay, Serkan; Özcan, Fırat; Aras, Dursun; Topaloğlu, Serkan (Wiley, 2022)
A 21 years old man presented with regular palpitations anddocumented both narrow and wide QRS complex tachycardia (NCTand WCT, respectively). At electrophysiological study, the retrogradeconduction was decremental and concentric with the earliestactivation site at the His bundle (HB) region. Para?Hisian pacingindicated retrograde conduction over the fast pathway of theatrioventricular (AV) node. After the AH interval jump, two WCTswith both right bundle branch block (RBBB) and left BBB (LBBB)BBB morphologies that spontaneously transform to an NCT wereobserved (Figure1). What are the possible mechanism of tachycar-dias and transition?
Keywords: Atrioventricular Nodal Reentrant Tachycardia; Narrow QRS; Wide QRS